Fostering Creativity and Innovation : Creating a Sustainable Innovation Environment in the United Arab Emirates - Lasrado, Flevy (Palgrave Macmillan, 2024)
Compiling best practices and original research, this book examines the factors that influence the sustainability of creativity and innovation in organisations and proposes a toolkit to assess gaps within existing strategy. Focusing particularly on the United Arab Emirates (UAE), the author offers practical suggestions for improving and enhancing innovation, and ultimately achieving results. Both creativity and innovation have become pillars for leveraging competitive advantage in recent years, and therefore this book is a vital read for anyone engaged in ensuring sustainable development in organisations, particularly those within the Middle East.